Saline Water Irrigation Through Drips and Sprinklers - Paliwal, K V (Annals of Arid Zone, 2016)
Saline water irrigation by drips and sprinklers has been examined in relation to crop response to saline water, upper limits of water salinity up to which these methods can be used for different soils and climatic conditions, and relative merits and demerits of these methods for different crops. Various aspects, viz, salt distribution under drip. leaf injury and absorption of nutrients by plants on sprinkling saline water and remedial measures have been discussed. Efficacy of drips and sprinklers has been compared with furrow/flood irrigation.